2022
DOI: 10.21608/asalexu.2022.246005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multimodality Chest Physiotherapy Interventions on Prevention of Ventilator Associated Pneumonia among Mechanically Ventilated Patients

Abstract: Background: Ventilator-Associated Pneumonia (VAP) refers to nosocomial pneumonia occurring 48 hours or more after initiation of mechanical ventilation (MV). Critically ill patients who is receiving mechanical ventilation may have an increased risk of VAP due to multiple factors as sputum retentions and atelectasis. Thus, different combinations of chest physiotherapy assist in the reexpansion of the atelectatic lung, confer short-term improvement in total lung-thorax compliance and expiratory flow rates, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…In the study by Younes et al (2022) in Egypt, more than half of the participants had an APACHE II score less than 20, which is not consistent with the results of the present study. Their study was intervention, and those with lung damage, such as pulmonary embolism, emphysema, and uncontrolled blood pressure, were not included in the study; therefore, there was a difference in the inclusion and exclusion criteria between the two studies [53].…”
Section: Discussioncontrasting
confidence: 99%
“…In the study by Younes et al (2022) in Egypt, more than half of the participants had an APACHE II score less than 20, which is not consistent with the results of the present study. Their study was intervention, and those with lung damage, such as pulmonary embolism, emphysema, and uncontrolled blood pressure, were not included in the study; therefore, there was a difference in the inclusion and exclusion criteria between the two studies [53].…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study showed that the APACHE II scores did not differ significantly between the intervention and control groups. Other studies also found no statistically significant difference between the two groups regarding the APACHE-II score [11,64]. The APACHE II score is a vital indicator of acute physiological abnormalities in patients [11,64].…”
Section: Discussionmentioning
confidence: 90%
“…Other studies also found no statistically significant difference between the two groups regarding the APACHE-II score [11,64]. The APACHE II score is a vital indicator of acute physiological abnormalities in patients [11,64]. The APACHE II score is a vital indicator of acute physiological abnormalities in patients [65,66].…”
Section: Discussionmentioning
confidence: 92%
“…Wang et al (2019) found that the incidence of ventilator associated pneumonia did not reduce by chest physiotherapy only, but multimodality chest physiotherapy may be an substitute respiratory rehabilitation program in ventilator patients based on individualized approach. Younes et al (2022) was also reported that using multimodality chest physiotherapy interventions had better effect on reduce risk for pneumonia, and improve oxygenation. In order to promote sputum clearance and improve oxygenation in ventilated patients, combining manual hyperinflation and ventilatory muscle endurance exercises with chest physical therapy may be beneficial (Ibrahim & Mohamed, 2018).…”
Section: Resultsmentioning
confidence: 96%